Using nonparametric analysis (DEA) for measuring technical efficiency in poultry farms - Heidari,MD (2011)
The objective of this study was to determine the economic efficiency of resource utilization in broiler production farms using a non-parametric production function, data envelopment analysis (DEA). Data for the analysis were collected from a cross section of 44 farmers using a multi-stage sampling procedure. In DEA models the farmers that produce their level of output with the least amount of input serve as benchmarks against which the input use inefficiency of all other farmers can be measured. The total variable costs, net return and benefit cost ratio were calculated to be 3506.29 $ (1000 bird)-1, 1386.53 $ (1000 bird) -1 and 1.38, respectively. The average values of technical and scale efficiencies of farmers were found to be 0.92 and 0.93. The results also revealed that about 10% of the total input resources could be saved if the farmers follow the input package recommended by the DEA.